Developmental network structure and support: gendered consequences for work–family strain and work–parenting strain in the Australian mining industry. Issue 10 (31st May 2019) - Parker, Polly; Cotton, Richard D.; Yates, Miriam S.; Baxter, Janeen; Arend, Susan
Abstract: Developmental networks enhance career success through the support received by the protégé via the network structure. This paper extends developmental network research by exploring the extent to which strain is associated with developmental network structure and support in the Australian mining industry, a highly volatile and unique context. Our research tests the popular notion of 'the more support you get, the better' which is in need of further exploration in the developmental networks literature particularly in specific work contexts with strain (vs. success variables) as outcomes. Results indicate that bigger, broader networks with more career, psychosocial and role modelling support are not always beneficial for protégés in this context. A smaller network with a broader range of developers is associated with reduced work–parenting strain, but not work–family strain. Increased career support reduced work–family strain, but this was not the case for increased psychosocial support and role modelling support. Further, gender moderated the relationship between psychosocial support and work–family strain possibly due to token group effects.